ANALISIS PROBLEMATIKA KETERAMPILAN MENYIMAK DALAM PEMBELAJARAN BAHASA INDONESIA PADA PESERTA DIDIK FASE C SEKOLAH DASAR - Rila Pangesthi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Listening skills are one of the fundamental aspects in learning Indonesian, especially in Phase C at the elementary school level which includes grades IV to VI. This skill plays an important role in building understanding, improving critical thinking, and supporting the development of other language skills such as speaking, reading, and writing. In reality, listening skills often receive less attention in classroom learning, which has an impact on students' understanding abilities. This study aims to analyze the importance of listening skills, factors that influence the effectiveness of listening learning, and strategies that can be applied to improve students' listening skills in elementary schools. The method used in this study is a quantitative descriptive approach based on data obtained to analyze problems with listening skills in the classroom. The results of the study show that listening skills can be influenced by internal and external factors. Internal factors include students' interests and motivations, cognitive abilities, and concentration when listening. Meanwhile, external factors include teacher teaching methods, learning environments, use of learning media, and distractions around students during the listening process. Listening skills can be improved through the use of interesting learning media, interactive methods such as discussion and reflection, and the application of technology-based learning strategies. The role of teachers in providing appropriate stimuli and creating a conducive learning environment also greatly influences the development of students' listening skills.